Assessing Dentists' Awareness and Practices in the Interplay Between Obesity and Periodontitis in Primary Health Care: A Questionnaire-Based Survey - Valeska Maria Souto Paiva Duarte; Vanessa Feitosa Alves; Edson Hilan Gomes de Lucena; Yuri Wanderley Cavalcanti; Sabrina Garcia de Aquino (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess the comprehension of dentists in Primary Health Care (PHC) regarding the interplay between obesity and periodontitis and evaluate the presence of practical approaches for managing these patients. Material and Methods: For this cross-sectional study, 187 general dental practitioners from different regions of Brazil were selected by convenience. A specific instrument was developed to assess the knowledge and practices of PHC dentists concerning this topic. The data underwent descriptive and analytical statistical analyses, followed by Poisson regression analysis with robust variance to test associations. Results: Regarding knowledge, most dentists have a limited understanding of the link between obesity and periodontitis, despite 43% recognizing the higher susceptibility of individuals with obesity to oral issues. About 20% of professionals considered their knowledge "adequate." Better knowledge was observed among dentists who worked only in the public sector, which has concluded some post-graduation (p<0.05). Regarding the professional's practical conduct, around 57% of the dentists do not diagnose obesity, and 64% of the professionals do not refer these patients to a nutritionist. Conclusion: The study's outcomes underscore the prevailing lack of awareness among this sampled group of dental practitioners concerning the association between obesity and periodontitis. Furthermore, it was observed that multidisciplinary treatment for obese patients within the realm of PHC is generally underperformed.